2014
DOI: 10.23818/limn.33.17
|View full text |Cite
|
Sign up to set email alerts
|

Single pass electrofishing method for assessment and monitoring of larval lamprey populations

Abstract: Single pass electrofishing method for assessment and monitoring of larval lamprey populationsOur work aims at calibrating and standardizing the single pass protocol of electrofishing to assess and monitor larval lamprey populations, mainly for European populations of sea lamprey (Petromyzon marinus). The method is considered cost-effective and appropriate for use both on the scale of management decisions (from river or watershed to a regional or national scale) and as a routine assessment tool as required by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Although controls for our salvage evaluations were intended to allow us to adjust for mortality associated with transport and laboratory holding (which was nonexistent within 24 h), these results could also elucidate mortality for larval lampreys salvaged before dewatering, since during a predrawdown salvage, larval lampreys would ideally be collected by lamprey‐specific electrofishing, transported, and released into a nearby watered area. Salvaging all larval lampreys before dewatering would be optimal but is often impractical or impossible because the dewatered habitat area could be large and capture probability of electrofishing is variable and consistently less than 100% (Christie and Goddard 2003; Steeves et al 2003; Silva et al 2014; Harris et al 2016). Results for our salvage treatments in the fall suggest that mortality of salvaged larval lampreys was minimal and excavated enclosures revealed that larval lampreys that remained burrowed throughout the salvage treatment were alive and appeared unharmed, suggesting minimal mortality associated with the salvage protocols examined.…”
Section: Discussionmentioning
confidence: 99%
“…Although controls for our salvage evaluations were intended to allow us to adjust for mortality associated with transport and laboratory holding (which was nonexistent within 24 h), these results could also elucidate mortality for larval lampreys salvaged before dewatering, since during a predrawdown salvage, larval lampreys would ideally be collected by lamprey‐specific electrofishing, transported, and released into a nearby watered area. Salvaging all larval lampreys before dewatering would be optimal but is often impractical or impossible because the dewatered habitat area could be large and capture probability of electrofishing is variable and consistently less than 100% (Christie and Goddard 2003; Steeves et al 2003; Silva et al 2014; Harris et al 2016). Results for our salvage treatments in the fall suggest that mortality of salvaged larval lampreys was minimal and excavated enclosures revealed that larval lampreys that remained burrowed throughout the salvage treatment were alive and appeared unharmed, suggesting minimal mortality associated with the salvage protocols examined.…”
Section: Discussionmentioning
confidence: 99%
“…Third, monitoring data should fill specific information gaps and inform important management decisions (Nichols and Williams 2006). Fourth, we emphasize that “[t]here is no sampling method that can be used or is optimal for all cases” (Silva et al 2014). Finally, the use of standardized survey protocols can facilitate comparisons with other larval lamprey surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of abundance (number of larval lampreys) and density (number of larval lampreys per unit area) SAMPLING AND SURVEYING LARVAL LAMPREYS have been used to evaluate trends over space and time (Table 3). If the goal is relative abundance across survey sites or times, then a standardized protocol for all survey sites may be a more logistically achievable method (e.g., Harvey and Cowx 2003;Slade et al 2003;Silva et al 2014Silva et al , 2016. If the goal is absolute abundance of larval lampreys, then rigorous mark-recapture (MR) or depletion studies are essential.…”
Section: What Are the Abundance And Density?mentioning
confidence: 99%
See 1 more Smart Citation